Pediatric dental sedation: challenges and opportunities - Nelson TM; Xu Z (Dove Medical Press, 2015)
Travis M Nelson, Zheng Xu Department of Pediatric Dentistry, University of Washington, Seattle, WA, USA Abstract: High levels of dental caries, challenging child behavior, and parent expectations support a need for sedation in pediatric dentistry. This paper reviews modern developments in pediatric sedation with a focus on implementing techniques to enhance success and patient safety. In recent years, sedation for dental procedures has been implicated in a disproportionate number of cases that resulted in death or permanent neurologic damage. The youngest children and those with more complicated medical backgrounds appear to be at greatest risk. To reduce complications, practitioners and regulatory bodies have supported a renewed focus on health care quality and safety. Implementation of high fidelity simulation training and improvements in patient monitoring, including end-tidal carbon dioxide, are becoming recognized as a new standard for sedated patients in dental offices and health care facilities. Safe and appropriate case selection and appropriate dosing for overweight children is also paramount. Oral sedation has been the mainstay of pediatric dental sedation; however, today practitioners are administering modern drugs in new ways with high levels of success. Employing contemporary transmucosal administration devices increases patient acceptance and sedation predictability. While recently there have been many positive developments in sedation technology, it is now thought that medications used in sedation and anesthesia may have adverse effects on the developing brain. The evidence for this is not definitive, but we suggest that practitioners recognize this developing area and counsel patients accordingly. Finally, there is a clear trend of increased use of ambulatory anesthesia services for pediatric dentistry. Today, parents and practitioners have become accustomed to children receiving general anesthesia in the outpatient setting. As a result of these changes, it is possible that dental providers will abandon the practice of personally administering large amounts of sedation to patients, and focus instead on careful case selection for lighter in-office sedation techniques. Keywords: conscious sedation, anesthesia, general, pediatrics